On self-dual constacyclic codes of length psover Fpm+uFpm - Hai Q. Dinh (2018)
© 2017 Elsevier B.V. The aim of this paper is to establish all self-dual λ-constacyclic codes of length p s over the finite commutative chain ring R=F p m +uF p m , where p is a prime and u 2 =0. If λ=α+uβ for nonzero elements α,β of F p m , the ideal 〈u〉 is the unique self-dual (α+uβ)-constacyclic codes. If λ=γ for some nonzero element γ of F p m , we consider two cases of γ. When γ=γ −1 , i.e., γ=1 or −1, we first obtain the dual of every cyclic code, a formula for the number of those cyclic codes and identify all self-dual cyclic codes. Then we use the ring isomorphism φ to carry over the results about cyclic accordingly to negacyclic codes. When γ≠γ −1 , it is shown that 〈u〉 is the unique self-dual γ-constacyclic code. Among other results, the number of each type of self-dual constacyclic code is obtained.